Mechanisms of Neuroprotection by Protein Disulphide Isomerase in Amyotrophic Lateral Sclerosis - Adam K. Walker; Julie D. Atkin (Neurology Research International)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterised by the progressive loss of motor neurons, leading to paralysis and death within several years of onset. Although protein misfolding is a key feature of ALS, the upstream triggers of disease remain elusive. Recently, endoplasmic reticulum (ER) stress was identified as an early and central feature in ALS disease models as well as in human patient tissues, indicating that ER stress could be an important process in disease pathogenesis. One important chaperone induced by ER stress is protein disulphide isomerase (PDI), which is both upregulated and posttranslationally inhibited by S-nitrosylation in ALS. In this paper, we present evidence from studies of genetics, model organisms, and patient tissues which indicate an active role for PDI and ER stress in ALS disease processes.